The World Karst Aquifer Mapping project: concept, mapping procedure and map of Europe - Chen, Zhao; Auler, Augusto S.; Bakalowicz, Michel; Drew, David; Griger, Franziska; Hartmann, Jens; Jiang, Guanghui; Moosdorf, Nils; Richts, Andrea; Stevanovic, Zoran; Veni, George; Goldscheider, Nico (Hydrogeology journal, 2017)
Karst aquifers contribute substantially to freshwater supplies in many regions of the world, but are vulnerable to contamination and difficult to manage because of their unique hydrogeological characteristics. Many karst systems are hydraulically connected over wide areas and require transboundary exploration, protection and management. In order to obtain a better global overview of karst aquifers, to create a basis for sustainable international water-resources management, and to increase the awareness in the public and among decision makers, the World Karst Aquifer Mapping (WOKAM) project was established. The goal is to create a world map and database of karst aquifers, as a further development of earlier maps. This paper presents the basic concepts and the detailed mapping procedure, using France as an example to illustrate the step-by-step workflow, which includes generalization, differentiation of continuous and discontinuous carbonate and evaporite rock areas, and the identification of non-exposed karst aquifers. The map also shows selected caves and karst springs, which are collected in an associated global database. The draft karst aquifer map of Europe shows that 21.6% of the European land surface is characterized by the presence of (continuous or discontinuous) carbonate rocks; about 13.8% of the land surface is carbonate rock outcrop.